Peran Teknologi AI dalam Mengembangkan Algoritma Media Sosial: Tantangan dan Peluangnya - Anugrah, Muhammad Dimas (Jurnal komunikan, 2024)
The development of artificial intelligence (AI) technology has opened new opportunities in the advancement of social media algorithms, enabling more personalized user experiences, more efficient content moderation, and more targeted advertisement management. This paper discusses the role of AI in personalization, moderation, and security within social media platforms, as well as challenges such as algorithmic bias, data privacy protection, and difficulties in understanding social context. Case studies on major platforms like Facebook, YouTube, Instagram, and Twitter illustrate how AI has enhanced services through content recommendations, misinformation detection, and user interaction management. Although the implementation of AI presents ethical and technical challenges, fair and transparent development can unlock new opportunities to create safer, more inclusive, and beneficial social media. Collaboration among developers, regulators, and society is necessary to ensure responsible AI implementation that positively contributes to the global digital ecosystem.